The Impact of Macroeconomic Variables on Firm Value: The Moderating Role of Expected Credit Loss in the Indonesian Banking Sector - Ahalik Ahalik; Dinar Titah Sepdyandini (Asia Pacific Journal of Management and Education (APJME), 2026)
This study investigates the impact of macroeconomic variables, namely inflation and the Rupiah exchange rate, on firm value as proxied by Price to Book Value (PBV) in listed commercial banks in Indonesia during 2021–2023. Expected Credit Loss (ECL) is incorporated as a moderating variable to capture risk management dynamics in the banking sector. Using a quantitative causal approach, secondary data from Bank Indonesia and the Financial Services Authority (OJK) were analyzed using multiple regression and Moderated Regression Analysis (MRA). The results indicate that inflation and the exchange rate do not have a significant direct effect on PBV. However, their interaction with ECL significantly influences firm value. These findings highlight the importance of incorporating credit risk reserves as a moderating factor when assessing the impact of macroeconomic conditions on firm value. The study contributes to behavioral finance literature and provides practical implications for banking risk management.